Implementation of Ion Exchange Processes for Carbon Dioxide Mineralization Using Industrial Waste Streams - Bustillos, Steven; Alturki, Abdulaziz; Prentice, Dale; La Plante, Erika Callagon; Rogers, Mitchell; Keller, Mark; Ragipani, Raghavendra; Wang, Bu; Sant, Gaurav; Simonetti, Dante A. (Frontiers in Energy Research, 2020)
Sequestration of CO2 within stable mineral carbonates (e.g. CaCO3) represents an attractive emission reduction strategy because it offers a leakage-free alternative to geological storage of CO2 in an environmentally benign form. However, the pH of aqueous streams equilibrated with gaseous streams containing CO2 (pH < 4) are typically lower than that which is required for carbonate precipitation (pH > 8). Traditionally, alkalinity is provided by a stoichiometric reagent (e.g., NaOH) which renders these processes environmentally hazardous and economically unfeasible. This work investigates the use of regenerable ion-exchange materials to induce alkalinity in CO2-saturated aqueous solutions such that the pH shift required for mineralization occurs without the need for stoichiometric reagents. Na+-H+ exchange isotherms (at [H+] = 10-8-10-1 M) and rates were measured for 13X and 4A zeolites and TP-207 and TP-260 organic exchange resins in batch equilibrium and fixed-bed exchange experiments, respectively. At solutions equilibrated with CO2 at 1 atm (pH = 4), H+ exchange capacities for the materials were similar (1.7-2.4 mmol H+ per g material) and resulted in pH increases from 4.0 to greater than 8. Multi-component mixtures using Ca2+ and Mg2+ cations (at 10-3-10-1 M) in CO2-saturated water were used to probe competitive ion exchange. The presence of divalent cations in solution inhibited H+ exchange, reducing capacities to as low as 0.2 mmol H+/g for both resins and zeolites. Dynamic H+ exchange capacities in fixed-bed ion exchange columns were similar to equilibrium values for resins ( 1.5 mmol/g) and zeolites ( 0.8 mmol/g) using inlet solutions that were equilibrated with gaseous streams of CO2 at 1 atm, however, exchange kinetics were limited by intraparticle diffusion as indicated by the increased rate parameters with increasing inlet flow rates (20-160 cm3 min-1). Experimental calcite precipitation from mixing the alkaline CO32–rich water solution obtained from the ion-exchange column with a simulated liquid waste stream solution achieved thermodynamic maximum yields. The results from these studies indicate that ion exchange processes can be used as an alternative to the addition of stoichiometric bases to induce alkalinity for the precipitation of CaCO3, thereby opening a pathway toward sustainable and economic mineralization processes.